Assessment of River Water Quality and Pollution Status Using Physicochemical and Biometrics, Awetu River, Ethiopia. (15th November 2022) - Ebsa, Dessalegn Geleta; Kabeta, Worku Firomsa
Abstract : The surface water is contaminated by a variety of synthetic organic and inorganic compounds, chemicals, and nutrients; due to this reason, the quality of the water resources of Ethiopia is declining at an alarming rate, resulting in severe environmental degradation. The main objective of the study was to recognize the pollution status river for the study area by physicochemical parameters and the extent of microbial environmental matrices. The experiment was conducted using a complete randomized model with three composite replicates in each site, and water samples were collected from six different sampling sites using the American Public Health Association (APHA) technique. Water quality parameters were analyzed by the standard method of examination, whereas same examination was determined on site (in situ) (pH, Temp, Conductivity, and Turbidity), whereas TSS, COD, BOD, nitrate, alkali, and orthophosphate were identified in the laboratory. The relationship between physicochemical and benthos assemblages as bio indicators of ecohydrological river water quality was investigated using Spearman's median rank correlation. The output of the study reveals that there was a negatively significant difference in effect between the sample and all the sites of the river. Physicochemical results of the river indicate Temp (23.62), EC (101.42), nitrate (2.175), and orthophosphates (0.081) were below the standard guidelines; however, turbidity (8.41), BOD (784.5), and alkali (396.5) were above the standard. Same of the water quality values for this study were ranges within the standard, DO (5.11), and pH (7.66). The benthos assemblage communities of the ecohydrological area were more influenced by the influents, and the macroinvertebrate index of all sample sites indicates the Shannon and Simpson diversity indices; result shows that the river was lightly polluted.